Body image is associated with leisure-time physical activity and sedentary behavior in adolescents: data from the Brazilian National School-based Health Survey (PeNSE 2015) - Gomes,Maria L.B. (2021)
Objective: To evaluate the association of leisure-time physical activity and sedentary behavior with body image concern and satisfaction in Brazilian adolescents. Methods: Data were extracted from the 2015 Brazilian National Adolescent School-based Health Survey (Pesquisa Nacional de Saúde do Escolar [PeNSE]). Information regarding body image concern and satisfaction, as well as exposures (physical activity and sedentary behavior) and covariates (maternal education, age, smoking, and alcohol intake), were assessed through a questionnaire. Results: Logistic regression analysis revealed that engagement in recommended levels of physical activity (≥ 300 min/week) was associated with a decreased concern with body image and a high satisfaction in boys. Four or more hours spent in sedentary activities were associated with increased concern with body image and dissatisfaction among boys and girls. Conclusion: These findings support the relevance of programs aiming to promote physical activity and reduce sedentary behavior in the adolescent population. Such programs play a protective role against body dissatisfaction and are important for the development of a healthy body image in adolescence.